Pengenalan Kosa Kata Bahasa Inggris Bermuatan Keislaman Melalui Lagu Religi - Zaitun Qamariah; Akhmad Ali Mirza; Muliana Setia Hapsari; Kholida Ziya; Mayra Musdalifah; Azhari Kurniawan (Jurnal Insan Pengabdian Indonesia, 2023)
The introduction of English vocabulary that integrates Islamic values is crucial for developing comprehensive English language proficiency in students. This dedication is focused on the goal of introducing English vocabulary with Islamic content to MIS Fathul Jannah students through religious songs. The approach used is an active and enjoyable learning model utilizing songs as a medium. Song selection is carried out through a selection process to adjust the difficulty level and learning needs. The results of the activity show a significant improvement in the mastery of English vocabulary by students after participating in this program. Thus, the introduction of English vocabulary through religious songs has proven to be effective in enhancing students' English language abilities while instilling deep-seated Islamic values. Programs like this can serve as an alternative in efforts to develop English language curricula based on religious values in schools.